2014
DOI: 10.3892/mmr.2014.2128
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) and angiotensin II induce the transdifferentiation of human endometrial epithelial cells in vitro

Abstract: Intrauterine adhesions (IUA) may be caused by endometrial stromal cell proliferation, increases in myofibroblasts or increases in extracellular matrix secretion. However, the specific mechanisms underlying the development of IUA have yet to be elucidated. The present study identified that angiotensin (Ang) II is capable of promoting endometrial epithelium cell (EEC) proliferation and the transdifferentiation of EECs into myofibroblasts. Furthermore, the present study found that Ang II increased the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…19 However, during fibrogenesis, endometrial epithelial cells undergo an EMT-like process when massive ECM generated from stromal cells accumulates in the endometrium, resulting in failure to regenerate functional endometrium. 20 The downregulation of miR29b was inversely correlated with uterine Smad3 levels in the present study, which is consistent with the results of other studies of renal fibrosis. It has been demonstrated that TGF-b1 negatively regulates miR-29b expression via Smad3 interaction with a Smad binding site at its promoter in response to TGFb1.…”
Section: Discussionsupporting
confidence: 93%
“…19 However, during fibrogenesis, endometrial epithelial cells undergo an EMT-like process when massive ECM generated from stromal cells accumulates in the endometrium, resulting in failure to regenerate functional endometrium. 20 The downregulation of miR29b was inversely correlated with uterine Smad3 levels in the present study, which is consistent with the results of other studies of renal fibrosis. It has been demonstrated that TGF-b1 negatively regulates miR-29b expression via Smad3 interaction with a Smad binding site at its promoter in response to TGFb1.…”
Section: Discussionsupporting
confidence: 93%
“…All in all, our present observations, as well as results from previous studies conducted on EC tumour samples, indicate a specific link between angiotensin effectiveness and cell differentiation status (2). Our observations are consistent with data presented by Shan et al, showing that Ang II is capable of promoting endometrial epithelium cell proliferation (6). Similar results on the effect of Ang II on cell proliferation and survival were obtained for breast cancer and prostate cancer (12,13).…”
Section: Discussionsupporting
confidence: 93%
“…The decreased adhesion was quite surprising, but it may have resulted from acquisition of a strong mesenchymal phenotype, in which cells detaching from the basal membrane do not undergo cell death but survive these stressful conditions. Ang II-induced EMT observed in our study was also described by other research groups (6,30). Shan et al recently showed that Ang II promotes activation of endometrial epithelium cells and significantly decreases the expression of E-cadherin, increasing the expression of SMA (6).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations